An assessment of impacts of extractive industries on Landscape: a case study of gypsum mining in Kajiado, Kenya - OMOTI; K. M; KITETU; J. J; KERIKO, J. M. (kabarak university, 2016)
Increased mining activities titanium, gypsum gold to ii. Mining Spurred by a progressive an aggressive long term iii. Mining activities are contributors to landscape biodiversity. 6th Annual International Research Conference Introduction / Background activities in Kenya, targeting to name a few progressive Constitution and development blueprint are potentially important landscape changes and loss of
Keywords: An assessment of impacts of extractive industries on Landscape; case study of gypsum mining in Kajiado, Kenya